Mengamati Aspek-Aspek Visual Pertunjukan Tari Sebagai Pengayaan Kajian Senirupa - Anis Sujana (ITB Journal Publisher, LPPM ITB, 2007)
According to the medium, arts can be classified into the art of visual, the art of hearing, and the art of words. Those included in the art of visual are dance and fine art, in the art of hearing is music and in the art of words is poetry. This paper describes one of the art of the visual